Technical, economic and social feasibility of using solar street lighting on campus - I Made Aditya Nugraha; I Gusti Made Ngurah Desnanjaya (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
A good and proper street lighting system on campus indirectly supports teaching and learning activities. However, these conditions still need to be developed at the Marine and Fisheries Polytechnic of Kupang due to the lack of these facilities. Therefore, a solar street lighting system was designed considering the good potential of solar energy in this region. The design of this system is carried out by measuring for a year, analyzing the energy potential, economics of the system, and the social impact of installing the system. The installation of solar street lighting on campus based on the results of an analysis of technical, economic, and social aspects gives good and feasible results. The results from the technical aspect provide that the utilization of this system provides a PR value of 85%, and can make savings of 15.99 MWh per year, and provide energy of 177.8 kWh per year. The results from the economic aspect of using this system provide an IRR value of 6%, SPBP for 8.93 years, and a net present value (NPV) of IDR 85,247,500.56. The results of the social aspects obtained from the respondents’ answers showed different and meaningful results (p<0.05) from all categories given to respondents.